Direct synthesis of aluminosilicate ITH zeolite in the presence of a small organic template - Luan, Huimin; Chen, Wei; Wu, Qinming; Zheng, Anmin; Meng, Xiangju; Baerdemaeker, Trees De; Parvulescu, Andrei-Nicolae; Müller, Ulrich; Xiao, Feng-Shou (Catalysis today, 2022)
Despite very successful synthesis of many pure silica or germanosilicate zeolites, there are still challenges for direct synthesis of their aluminosilicate forms. As a typical example, it is easy to synthesize germanosilicate ITH, but difficult for direct synthesis of its aluminosilicate form. Recently, cationic oligomer has been successfully templated for direct formation of aluminosilicate ITH, but relatively complex steps for controlling molecular weight of the cationic oligomer strongly hinder the practical production of zeolite products. Herein, it is shown an alternative route for direct synthesis of aluminosilicate ITH zeolite in the presence of a small organic template with both structural directing ability for the ITH structure and strong interaction ability to aluminum species. Characterizations of the zeolite products with Si/Al ratios from 46 to 148 show high crystallinity, nanosheet-like crystal morphology, large microporous surface area (338 m2/g), high micropore volume (0.16 cm3/g), four-coordinated Al species, controllable acidic sites, and extraordinary hydrothermal stability (hydrothermal aging at 800 °C for 5 h with 10% water steaming). Catalytic tests in methanol-to-propylene (MTP) show that the aluminosilicate ITH zeolite has higher selectivity for propylene than that of commercial ZSM-5 zeolite with similar Si/Al ratio, which provides a candidate catalyst for MTP reaction in the near future. [Display omitted] •A small organic template is used for direct synthesis of aluminosilicate ITH zeolite.•It is easy to prepare the small organic template from commercially available compounds.•Aluminosilicate ITH zeolite has excellent performances in methanol-to-olefin reaction.